QAZIB OLINGAN BO‘SHLIQNI TO‘LDIRISHDA BOYITISH FABRIKALARI CHIQINDILARIDAN FOYDALANIB RUDA SIFATSIZLANISH KOʻRSATKICHINI KAMAYTIRISHGA ERISHISH - Xasanov, O.A.; Berdiyeva, D.X. (SCIENCE and SOCIETY, 2025)
The article discusses the development system used at the Kovuldi gold mine, owned by the Almalyk Mining and Metallurgical Combine joint-stock company, i.e. backfilling of mined-out space using a methodology for selecting the composition of backfill materials were considered during backfill mining operations and the possibility of technical application.